Two-dimensional semiconducting covalent organic frameworks via condensation at arylmethyl carbon atoms - Shuai Bi (Nature Portfolio, 2019)
Semiconducting covalent organic frameworks (COF) with conjugated structures are desired for optoelectric conversion but poor reversibility of bond forming reactions hampers the formation of crystalline structures. Here, the authors synthesise COFs with disubstituted C = C linkages which enable water splitting under visible light irradiation.